Description of two new species of anual fishes of the of the Hypsolebias antenori species group (Cyprinodontiformes: Rivulidae), from Northeast Brazil. - Nielsen, Dalton (2016)
To edit content in ZooBank that was created by other users, you must be sponsored by an existing ZooBank Editor, and/or become a recognized ZooBank Editor yourself. Sponsorship entails establishing a line of reference, with the sponsor agreeing to support your statement of your professional code of conduct and capability in editing this global resource. We welcome editorial input, but request clear lines of communication and an agreement to adhere to established professional standards. Please contact the ZooBank webmaster by email at admin[at]zoobank.org to learn more.